The Process Of Complexing The Criminal Action Of Planning Murder Performed By Police Investigators - Andi Mohamad Akbar Mekuo; Amin Purnawan (Law Development Journal, 2021)
The police is a figure and protector of the community who at the same time as law enforcement officers have committed a crime that is burdensome and disturbing to the community, namely eliminating a person's life through a planning process that contains elements of violating Article 340 of the Criminal Code for his actions that are declared no longer fit to carry out the police profession in accordance with the Decree. National Police Chief KEP/23VII/2003 concerning the Code of Ethics for the Republic of Indonesia Police. The objectives of the problem in this study are 1) To examine and analyze the settlement of criminal acts committed by unscrupulous members of the Police? 2) To examine and analyze the strategies that need to be taken by the Police to build its image in tackling criminal acts committed by unscrupulous members of the Police? The research approach method used is normative juridical. Sources of data used are secondary data and primary data, secondary data in this study refers to the literature and primary data refers to facts in the field and the results of interviews. The results of the study: 1) Settlement of violations of the police professional code of ethics that resulted in a criminal act will be processed first in a disciplinary hearing due to a dead line or time limit for the implementation of a disciplinary hearing, which is a maximum of 30 (thirty) days as in Article 19 of the Decree of the National Police Chief No. Pol Kep/44/IX/2004. After the implementation of the disciplinary hearing is completed, a trial will be held in the scope of the general court in accordance with Article 2 of PP NO. 3 of 2003 concerning the Implementation of Technical Institutional General Courts for Members of the Indonesian Police,